LAJU HIDROLISIS HEROIN DALAM AIR DAN PLASMA - I M. A. G. Wirasuta; M. A. Ningtyas; E. I. Setyawan (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2019)
Heroine is hydrolyzed spontaneously in water and plasma. This will influence the determination, especially on the drug profiling. Spectrophotodensitometry has been used to analyze drug profiling of illicit heroine. This article reports the AL-TLC separation of heroine, 6-monoacetylmorphine (6-MAM), morphine, acetyl codeine, and the heroine hydrolysis in water and plasma. Heroin, 6-MAM, morphine, and acetyl codeine can be well-separated by mobile phase of toluene:siclohexane:diethyl amine (75:15:10, v/v). The limit of detection was 165.16 ng/spot and the limit of quantification was 550.55 ng/spot. Heroine was hydrolyzed in water and plasma under first order reaction. The rate of reaction was 0.55 min-1 in water with the half time reaction of 12.47 minutes. On the other hand the hydrolysis rate in plasma was slower with the half time of 16 minutes. Keywords : hydrolysis, heroin, water, TLC-spectrophotodensitometer